MANAJEMEN KONFLIK DALAM TIM EDUPRENEUR SEBAGAI KATALISATOR INOVASI DI MI - Fauzi, Hasan; Salim, Muhlisin (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
The purpose of this study is to analyze the forms of conflict, management strategies, and their role as catalysts for innovation within the edupreneur team at MI Roudlotul Huda Terban. The research method used was qualitative with a case study approach. Data were collected through in-depth interviews with foundation administrators, madrasah principals, and teachers, as well as participant observation and documentation studies. Data analysis followed the interactive model of Miles and Huberman. The results showed that: (1) The forms of conflict that emerged consisted of substantive conflicts, such as tensions between teachers' pedagogical visions and the foundation's commercial orientation, as well as affective conflicts resulting from generational dynamics within the team; (2) The effective conflict management strategy implemented was a collaborative approach colored by Islamic values, such as deliberation to find the best solution (mashlahah), strengthening ties, and making congregational prayer a medium for shared reflection; (3) This constructively managed conflict proved to be a catalyst that triggered a number of important innovations, including the birth of the "Creative Student Market" program that teaches the principles of muamalah, the adoption of an integrated digital payment system, and the development of a more interactive tahfiz learning module. The conclusion of this study is that in the context of MI Roudlotul Huda Terban, conflict is not avoided but rather managed productively with value-based strategies, which ultimately encourages the creation of strategic innovations for the advancement of the madrasah. ABSTRAKTujuan penelitian ini adalah untuk menganalisis bentuk konflik, strategi manajemen, dan perannya sebagai katalisator inovasi dalam tim edupreneur di MI Roudlotul Huda Terban. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dengan pengurus yayasan, kepala madrasah, dan guru, serta observasi partisipan dan studi dokumentasi. Analisis data mengikuti model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa: (1) Bentuk konflik yang muncul terdiri dari konflik substantif, seperti ketegangan antara visi pedagogis guru dengan orientasi komersial yayasan, serta konflik afektif akibat dinamika generasi dalam tim; (2) Strategi manajemen konflik yang efektif diterapkan adalah pendekatan kolaboratif yang diwarnai nilai-nilai Islam, seperti musyawarah untuk mencari solusi terbaik (mashlahah), mempererat silaturahmi, dan menjadikan shalat berjamaah sebagai media refleksi bersama; (3) Konflik yang dikelola secara konstruktif ini terbukti menjadi katalisator yang memicu sejumlah inovasi penting, di antaranya lahirnya program "Pasar Siswa Kreatif" yang mengajarkan prinsip muamalah, adopsi sistem pembayaran digital yang terintegrasi, dan pengembangan modul pembelajaran tahfiz yang lebih interaktif. Simpulan dari penelitian ini adalah bahwa dalam konteks MI Roudlotul Huda Terban, konflik tidak dihindari melainkan dikelola secara produktif dengan strategi berbasis nilai, yang pada akhirnya justru mendorong terciptanya inovasi-inovasi strategis bagi kemajuan madrasah.